A Case of Guillain-Barré Syndrome Associated With COVID-19 - Kartikeya Rajdev MBBS; Navin Victor MD; Elaine S. Buckholtz MD; Praveen Hariharan MBBS; Muhammad Ahsan Saeed MD; Daniel M. Hershberger MD; Sabin Bista MBBS (SAGE Publishing, 2020)
A novel member of human RNA coronavirus, which is an enveloped betacoronavirus, has been termed severe acute respiratory syndrome coronavirus-2 (SARS COV-2). The illness caused by SARS COV-2 is referred to as the coronavirus disease 2019 (COVID-19). It is a highly contagious disease that has resulted in a global pandemic. The clinical spectrum of COVID-19 ranges from asymptomatic illness to acute respiratory distress syndrome, septic shock, multi-organ dysfunction, and death. The most common symptoms include fever, fatigue, dry cough, dyspnea, and diarrhea. Neurological manifestations have also been reported. However, the data on the association of Guillain-Barré syndrome (GBS) with COVID-19 are scarce. We report a rare case of a COVID-19-positive 36-year-old immunocompromised male who presented with clinical features of GBS. His clinical examination showed generalized weakness and hyporeflexia. The cerebrospinal fluid (CSF) analysis showed albuminocytological dissociation. Intravenous immunoglobulin (IVIG) was administered based on the high clinical suspicion of GBS. The patient's neurological condition worsened with progression to bulbar weakness and ultimately neuromuscular respiratory failure requiring mechanical ventilation. His nerve conduction studies were consistent with demyelinating polyneuropathy. He received five plasma exchange treatments and was successfully weaned from mechanical ventilation. A brain and cervical spine magnetic resonance imaging was obtained to rule out other causes, which was normal. COVID-19 is believed to cause a dysregulated immune system, which likely plays an important role in the neuropathogenesis of GBS.